Entrepreneurial Marketing Skills and Small-Scale Business Performance: The Case of Ghana - Ayiku, Andrews; Grant, E. Stephen (Journal of Comparative International Management)

(untitled) (Management Futures, 2021)
The development of SMEs serves as a tool for creating employment opportunities in developing countries. SME growth can be attributed to how owners and managers use entrepreneurial marketing skills in their day-to-day operations. A quantitative study was used to gain an understanding of the application of marketing skills in SMEs and the development of SMEs in Ghana. Findings indicate that entrepreneurs acquire marketing skills during their years of operation, however, these skills are not in tune with modern business trends and market competition. Establishing marketing departments and equipping business owners with marketing skills enables their ability to deal with volatile consumer demands. Likewise, requisite marketing skills enable market understanding, new marketing approaches, and the design of demand driven products and services